PERBEDAAN EFEKTIFITAS PIJAT LAKTASI DENGAN PERAWATAN PAYUDARA TERHADAP KEBERHASILAN MENYUSUI DI PMB KOTA PEKANBARU - Octa Dwienda Ristica; Rita Afni (LPPM Universitas Abdurrab, 2024)
International Guidelines, which are based on scientific data about the advantages of breast milk for infants, moms, families, and nations, advise exclusive breastfeeding for six months. The sensation of having inadequate or too little breast milk, breast swelling, flat or painful nipples, clogged breast milk ducts, and mastitis are issues that nursing moms often face. Breast care and lactation massage are two of the numerous strategies that may be used to boost breast milk supply. The purpose of this study is to ascertain how lactation massage and breast care vary in their ability to support successful breastfeeding in PMB Pekanbaru City. The study design used was two group independent approach design, and the research methodology was quasi experimental (quasi experimental). Mothers who had given birth within two hours and were nursing in the Pekanbaru Midwife Independent Practice Work Area made up the study population. The present study used the independent T test for analysis in order to ascertain the impact of lactation massage and breast care on postpartum moms' success in breastfeeding. The average amount of breast milk provided to moms who undergo lactation massage is 5.47 months, with a standard deviation of 0.837, according to the findings of statistical data processing using the Independent Samples Test. Breastfeeding moms give birth to their children for 4.6 months on average, with a standard deviation of 1,352. Breast milk is delivered to women who do breast care